PENGARUH LAMA THAWING DALAM AIR ES (3°C) TERHADAP PERSENTASE HIDUP DAN MOTILITAS SPERMATOZOA SAPI BALI (Bos sondaicus) - Achmad Jaelani; M. Irwan Zakir; abdul Azis (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2014)
The  aim  of  this  study  was  to  find  out  effect  of    thawing  lenght    in  ice  water  (3oC)  to  viability and motility of Bali’s cattle spermatozoa’s. This research was conducted in Februari 2014 at  Balai  Inseminasi  Buatan  Laboratory  in  Banjarbaru  Kalimantan  Selatan.  The  treatment  was thawing  lenght  at  30,60,90  and  120  minutes.  Each  treatment  needed  3  dose  straw  and    3 replication. Live percentage  (%)  and  motility  were perceived from the study. Data analysis used DMRT  test.  The  result  showed  thawing  lenghtwere  significantly  effect  on  viability  and  not significant on motility of Bali cattle spermatozoa . Keywords : thawing lenght, viability and motility